Method for evaluating gas production performance of lithium-rich manganese-based positive electrode material and application of method

By preparing and assembling a buckle half-cell, using specific relationships and high-temperature side reactions, the gas production performance of lithium-rich manganese-based cathode materials is quickly evaluated, solving the problems of difficulty and high cost in the existing technology, and achieving rapid and accurate gas production performance evaluation.

CN119595843APending Publication Date: 2025-03-11TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411826487.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and effectively evaluate the gas production performance of lithium-rich manganese-based positive electrode materials, especially at high voltages, which leads to unstable materials and is prone to side reactions with the electrolyte, resulting in large quantities of gas production, limiting its application in battery cells.

Method used

By preparing lithium-rich positive electrode sheets and assembling them into a buckle half-cell, the specific relationship is met by using factors such as electrode sheet density, porosity, electrolyte titration and high-temperature side reactions, and the number of cycles before diving is evaluated, so as to quickly evaluate the gas production performance of lithium-rich manganese-based positive electrode materials.

Benefits of technology

The gas production performance of lithium-rich manganese-based cathode materials is achieved quickly and accurately, reducing the evaluation cost and cycle, and is suitable for materials containing and without cladding, expanding the scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595843A_ABST
    Figure CN119595843A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a method for evaluating the gas production performance of a lithium-rich manganese-based positive electrode material and application of the method. The evaluation method comprises the following steps: preparing the lithium-rich manganese-based positive electrode material into a lithium-rich positive electrode plate with the surface density of A, the porosity of B and the radius of D; dropwise adding an electrolyte with the volume of C onto the lithium-rich positive pole piece and the diaphragm, and assembling into a button type half cell; 10 < = pi * D2 * A * 100B / C < = 25; the cycle index of the button type half-cell before diving has a corresponding relationship with the gas production rate of the lithium-rich manganese-based positive electrode material, and the gas production performance of the lithium-rich manganese-based positive electrode material is evaluated through the corresponding relationship between the cycle index of the button type half-cell before diving and the gas production rate of the lithium-rich material. According to the method, the surface and interface stability of the lithium-rich manganese-based positive electrode material containing the coating layer or not containing the coating layer can be rapidly evaluated, and the gas production performance of the lithium-rich manganese-based positive electrode material can be rapidly evaluated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for evaluating the gas production performance of a lithium-rich manganese-based positive electrode material and an application thereof. Background Art

[0002] As the most popular cathode material in current research, lithium-rich manganese-based cathode materials have the advantages of high specific capacity (>250mAh / g), low preparation cost and abundant raw materials. With the increasing investment in the research and development of solid-state and semi-solid-state batteries in recent years, lithium-rich manganese-based cathode materials have become a hot competitive material.

[0003] However, the high capacity characteristics of lithium-rich manganese-based cathode materials can only be exerted under high voltage, which will cause the instability of the materials, making it easy for the battery cell to react with the electrolyte during use, resulting in a large amount of gas production. The serious gas production problem limits the application of lithium-rich materials in batteries. Solving the gas production problem of lithium-rich materials under high voltage has become a research focus of lithium-rich manganese-based cathode materials. At present, surface coating of lithium-rich manganese-based cathode materials to improve the surface and interface stability of lithium-rich manganese-based cathode materials is an effective method to improve the gas production of lithium-rich materials. Establishing a method for quickly evaluating the gas production performance of lithium-rich manganese-based cathode materials can greatly improve the research and development process of lithium-rich materials.

[0004] At present, the main methods for improving lithium-rich manganese-based positive electrode materials include regulating the composition of lithium-rich materials, regulating the morphology of materials, constructing heterogeneous structures on the surface of materials, and stabilizing and coating the surface of materials. Among them, there are many conclusions about the relationship between the composition, morphology and electrochemical performance of materials and gas production performance. For example, the specific surface area of ​​the material is related to the gas production performance of the material. The larger the specific surface area, the larger the contact area between the electrolyte and the positive electrode surface, and the corresponding gas production. The coating is a method of further improving the gas production performance of the material based on material composition screening and morphology adjustment. The performance of the substrate is similar, and the gas production characteristics of lithium-rich materials cannot be directly judged by the specific surface area. Therefore, it is necessary to develop a method that can quickly evaluate the gas production performance of lithium-rich materials with a coating layer.

[0005] At present, the most intuitive method to evaluate the gas production performance of lithium-rich batteries is to prepare soft-pack batteries by matching lithium-rich materials with negative electrodes, and then perform chemical composition and capacity cycles, and determine the gas production performance of lithium-rich materials by observing and measuring the volume changes of gas bags. However, this method has the following defects: (1) High preparation cost: The preparation of a full battery requires a large amount of lithium-rich materials and high battery preparation costs, and a stricter quality management system is required to ensure the normal value of the battery; (2) Long preparation and testing cycle: The preparation and testing of the full battery needs to be carried out according to a strict set of processes, and the preparation and testing cycle is long; (3) High equipment requirements: Generally, the equipment requirements for the preparation of full batteries and full battery testing are high. If there is no complete battery line, it is difficult to achieve the preparation and testing of the full battery. All of the above factors will greatly delay the progress of lithium-rich material development and cause a lot of cost investment.

[0006] The performance of lithium-rich manganese-based positive electrode materials can be quickly evaluated using simple and easy-to-prepare button half-cells. However, due to the unique structure of the button half-cell, the gas production performance of the lithium-rich manganese-based positive electrode materials cannot deform like soft-pack batteries. Therefore, it is not feasible to determine the gas production performance of lithium-rich materials by observing the expansion of the button half-cell.

[0007] Therefore, it is of great significance to develop a method that can quickly evaluate the gas production performance of lithium-rich manganese-based cathode materials.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The first purpose of the present invention is to provide a method for evaluating the gas production performance of lithium-rich manganese-based positive electrode materials, which can quickly evaluate the surface and interface stability of lithium-rich manganese-based positive electrode materials with or without coating layers, and quickly evaluate the gas production performance of lithium-rich manganese-based positive electrode materials. The method solves the difficulties in evaluating the gas production performance of lithium-rich manganese-based positive electrode materials and the high cost, long cycle and high equipment requirements of matching lithium-rich materials with negative electrodes to make soft-pack batteries.

[0010] The second object of the present invention is to provide an evaluation method for the gas generation performance of lithium-rich manganese-based positive electrode materials and its application in the preparation of lithium batteries.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] The present invention first provides a method for evaluating the gas production performance of a lithium-rich manganese-based positive electrode material, comprising the following steps: preparing the lithium-rich manganese-based positive electrode material into a lithium-rich positive electrode plate; the surface density of the lithium-rich positive electrode plate is A, in units of mg / cm 2; The porosity of the lithium-rich positive electrode plate is B; The shape of the lithium-rich positive electrode plate is circular, and the radius of the lithium-rich positive electrode plate is D, in cm; The electrolyte is dripped onto the lithium-rich positive electrode plate and the separator, and assembled into a button half-cell; wherein the volume of the electrolyte in the button half-cell is C, in uL; A, B, C, D satisfy the following relationship: 10≤π×D 2 ×A×100B / C≤25; the gas production performance of the lithium-rich manganese-based positive electrode material is evaluated by the number of cycles before the button half-cell undergoes water diving.

[0013] Furthermore, the A is 8 to 15 mg / cm 2 ;

[0014] Furthermore, the B is 35% to 40%.

[0015] Furthermore, the button half-cell is pre-charged and pre-discharged, and then stored at high temperature for a period of time to obtain a battery after high-temperature storage; the battery after high-temperature storage is activated and then subjected to a high-temperature and high-voltage cycle test, and then the gas production performance of the lithium-rich manganese-based positive electrode material is evaluated by the number of cycles of the high-temperature and high-voltage cycle test before water diving occurs.

[0016] Furthermore, the method of pre-charging and pre-discharging treatment includes: charging the button half-cell to 4.4-4.5V, and then discharging it to 3.0-3.5V.

[0017] Furthermore, the high temperature storage temperature is 60-80°C.

[0018] Furthermore, the high temperature storage time is 2 to 10 hours.

[0019] Furthermore, the activation method includes: performing the activation at a temperature of 45° C., a voltage range of 2.0 to 4.8 V, and a charge and discharge rate of 0.05 to 0.1 C.

[0020] Furthermore, the ambient temperature of the high temperature and high voltage cycle test is 45±1°C.

[0021] Furthermore, the voltage range of the high temperature and high voltage cycle test is 2.0 to 4.6 V, and the charge and discharge rate is 0.33 to 1.0 C.

[0022] Furthermore, by comparing the number of cycles of batteries containing different lithium-rich manganese-based positive electrode materials before water diving occurs, the gas production performance of the lithium-rich manganese-based positive electrode material is determined.

[0023] The present invention also provides the application of the method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material in the preparation of lithium batteries.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided by the present invention can quickly evaluate the surface and interface stability of the lithium-rich manganese-based positive electrode material and the gas production performance of the lithium-rich manganese-based positive electrode material by using a simple and easy-to-prepare button half-cell and utilizing the relationship between the electrode surface density, electrode porosity, electrolyte drop amount, high-temperature side reactions of the electrolyte and the lithium-rich manganese-based positive electrode material, and the cycle diving phenomenon. The method is applicable to both lithium-rich manganese-based positive electrode materials containing a coating layer and lithium-rich manganese-based positive electrode materials without a coating layer, and has a wide range of applications.

[0026] (2) The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided by the present invention has accurate and effective evaluation results, and the evaluation speed is fast, the time used is short, and the method is simple and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a comparison chart of the cycle curves of the button-type half-cells of Example 1, Examples 11 to 15 and Comparative Example 3 provided by the present invention. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0030] Unless otherwise specified, in the present invention, "the first aspect", "the second aspect", "the third aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0031] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0032] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0033] In the first aspect, the present invention provides a method for evaluating the gas production performance of a lithium-rich manganese-based positive electrode material, and also a method for testing the surface and interface stability of a lithium-rich manganese-based positive electrode material, which specifically comprises the following steps:

[0034] The lithium-rich manganese-based positive electrode material is made into a lithium-rich positive electrode plate.

[0035] The surface density of the lithium-rich positive electrode is A, expressed in mg / cm 2 .

[0036] The porosity of the lithium-rich positive electrode plate is B.

[0037] The shape of the lithium-rich positive electrode plate is circular, and the radius of the lithium-rich positive electrode plate is D, in cm.

[0038] Then, an electrolyte is dripped onto the lithium-rich positive electrode plate and the separator, and assembled into a button-type half-cell, wherein the volume of the electrolyte in the button-type half-cell is C, in units of uL.

[0039] The above A, B, C, and D satisfy the following relationship: 10≤π×D 2 ×A×100B / C≤25. Among them, π×D 2 The value of ×A×100B / C includes, but is not limited to, any one of 10, 11, 12, 13, 14, 15, 16, 18, 20, 22, 23, 25 point values ​​or a range of values ​​between any two of them.

[0040] The number of cycles before the button-type half-cell dives has a corresponding relationship with the gas production of the lithium-rich manganese-based positive electrode material. The gas production performance of the lithium-rich manganese-based positive electrode material is evaluated by the number of cycles before the button-type half-cell dives.

[0041] It is understandable that the number of cycles before the battery dives is inversely proportional to the consumption of electrolyte. The more electrolyte is consumed, the greater the gas production of the battery.

[0042] The present invention uses a simple and easy-to-prepare button half-cell, and utilizes the relationship between the pole sheet surface density, pole sheet porosity, electrolyte drop amount, high-temperature side reaction of electrolyte and lithium-rich manganese-based positive electrode material, and cycle diving phenomenon to satisfy the specific relationship 10≤π×D 2 ×A×100B / C≤25, a method for quickly evaluating the gas production performance of lithium-rich manganese-based positive electrode materials was constructed. This method can quickly evaluate the surface and interface stability of lithium-rich manganese-based positive electrode materials, and quickly evaluate the gas production performance of lithium-rich manganese-based positive electrode materials. The problem of high cost, long cycle and high equipment requirements in the existing technology of matching lithium-rich materials with negative electrodes to make soft-pack batteries is solved, and the gas production performance of lithium-rich materials cannot be determined by observing the expansion of button-type half-cells.

[0043] The method is applicable to lithium-rich manganese-based positive electrode materials with a coating layer and lithium-rich manganese-based positive electrode materials without a coating layer, and has a wide range of applications. It can solve the problem in the prior art that the gas generation characteristics of lithium-rich materials cannot be directly determined by specific surface area due to similar performance of the substrates.

[0044] Specifically, the side reaction between the surface interface of the lithium-rich manganese-based positive electrode material and the electrolyte is one of the main sources of gas production in lithium-rich batteries. The lithium-rich manganese-based positive electrode material with unstable surface interface will react more seriously with the electrolyte, resulting in a large amount of electrolyte loss, that is, the amount of electrolyte loss is positively correlated with the stability of the lithium-rich manganese-based positive electrode material, and the consumption of electrolyte will cause a rapid dive of the lithium-rich button half-cell. Therefore, the present invention evaluates the gas production performance of the lithium-rich manganese-based positive electrode material through the normal cycle number of the lithium-rich button half-cell.

[0045] More specifically, the applicant found that the surface density of the lithium-rich positive electrode sheet, that is, the thickness of the electrode sheet, will affect the accuracy of the experimental results. Among them, if the surface density of the electrode sheet is too small, that is, the electrode sheet is too thin, the experimental error will be larger, and the accuracy of the experimental results will be low; within a certain range, increasing the surface density of the electrode sheet, that is, increasing the thickness of the electrode sheet, can reduce the experimental error, but if the surface density of the electrode sheet is too large, that is, the electrode sheet is too thick, it will be difficult to coat and it will also be easy to peel off from the current collector. Therefore, the present invention controls the surface density of the lithium-rich positive electrode sheet to satisfy the relationship 10≤π×D 2 ×A×100B / C≤25 to improve the accuracy of the experimental results and reduce experimental errors.

[0046] Furthermore, by controlling the porosity of the lithium-rich positive electrode plate, it is easy to adjust the amount of electrolyte titration required to completely wet the plate, avoiding interference with the experiment caused by excessive or insufficient electrolyte, thereby improving the accuracy of the experimental results. At the same time, the higher the porosity, the larger the contact area of ​​the electrolyte and the positive electrode plate for side reactions, and the faster the electrolyte is consumed. Therefore, the regulation of the porosity also facilitates the control of the contact area between the positive electrode plate and the electrolyte, which is directly related to the gas production of the battery, and is conducive to further improving the accuracy of the experimental results.

[0047] Furthermore, under certain electrode conditions, the greater the amount of electrolyte added, the lower the possibility of electrolyte shortage during the cycle, and the number of cycles will increase accordingly. Therefore, the present invention controls the amount of electrolyte added to satisfy the relationship 10≤π×D 2 ×A×100B / C≤25, which can speed up the evaluation process and shorten the evaluation time.

[0048] In some specific embodiments, the preparation method of the lithium-rich positive electrode sheet can adopt any method commonly used in the art, and the present invention is not limited to this. For example, the lithium-rich manganese-based positive electrode material can be evenly mixed with a binder, a conductive agent and a solvent to obtain a positive electrode slurry, and then the positive electrode slurry can be coated on the positive electrode collector and then dried.

[0049] In some specific embodiments, the A is 8 to 15 mg / cm 2 ; Including but not limited to 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 、15mg / cm 2 Any point value in or any range of values ​​between them.

[0050] It is understandable that during the coating process, the actual coated electrode will have a certain deviation. For example, the designed surface density is 5m 2 / g, the actual coating range is 4.5m 2 / g~5.5m 2 / g; therefore, increasing the coating surface density is beneficial to reducing experimental errors, but it is difficult to coat thicker pole pieces in button-type half-cells, and too thick a surface density will also make the rolling step difficult. Therefore, the present invention controls the surface density of the lithium-rich positive pole piece to 8-15 mg / cm 2 .

[0051] Within a certain range, the greater the surface density of the electrode, the more electrolyte is required per unit area (the greater the surface density, the more pores, the greater the injection volume), the more accurate the control of the electrolyte titration, and the smaller the experimental error. Therefore, the surface density of the lithium-rich positive electrode is preferably 10-15 mg / cm 2 .

[0052] In some specific embodiments, B is 35% to 40%, including but not limited to any point value of 35%, 36%, 37%, 38%, 39%, 40% or a range of values ​​between any two of them.

[0053] In some specific embodiments, the lithium-rich positive electrode plate is prepared by roller pressing. Rolling can adjust the porosity of the plate, and by controlling the porosity of the plate, the contact surface between the active material and the electrolyte in the plate is controlled to control the reaction. The above surface density and porosity can meet the titration requirements of the electrolyte while avoiding obvious deformation of the plate.

[0054] In some specific embodiments, C is 30 to 60uL, including but not limited to any one of 30uL, 35uL, 40uL, 45uL, 50uL, 55uL, and 60uL, or a range between any two of them. 30 to 60uL refers to the total amount of electrolyte added to the button half-cell, and the electrolyte can be added in batches during the actual implementation process.

[0055] In some specific implementations, taking the addition of 30 to 60 uL of electrolyte as an example, 15 to 30 uL of electrolyte is firstly added to the surface of the lithium-rich positive electrode plate, and then a diaphragm is covered on the upper surface of the positive electrode plate, and 15 to 30 uL of electrolyte is added to the diaphragm, which can accelerate the penetration of the electrolyte.

[0056] Among them, the titration amount of the electrolyte has a certain correlation with the surface density of the electrode. Excessive electrolyte will cause differences in the entire evaluation system. Therefore, the titration amount of the electrolyte is also an important factor affecting the evaluation results.

[0057] It is understandable that the amount of electrolyte added can be set according to the surface density of the lithium-rich positive electrode. In theory, the greater the surface density, thickness, and porosity of the electrode, the greater the demand for electrolyte filling the electrode. It is also possible to form an experimental gradient to screen the optimal amount of electrolyte added.

[0058] In some specific implementations, a rubber-tipped dropper with a scale can be used to control the amount of electrolyte added, and the required amount can be measured.

[0059] In some specific implementations, D is 0.6 cm to 0.7 cm.

[0060] In some specific embodiments, the diameters of the negative electrode sheet in the button half-cell and the lithium-rich positive electrode sheet are the same.

[0061] In some specific embodiments, the button-type half-cell is pre-charged and pre-discharged, and then stored at high temperature for a period of time, for example, 2 to 10 hours, to obtain a high-temperature stored battery. The high-temperature stored battery is then activated, and then subjected to a high-temperature and high-voltage cycle test, and the gas generation performance of the lithium-rich manganese-based positive electrode material is evaluated by the number of cycles before the high-temperature stored battery undergoes a water drop (i.e., before rapid attenuation).

[0062] Among them, pre-charging and pre-discharging the button half-cell can pre-form a film on the surface of the lithium-rich manganese-based positive electrode material particles, thereby reducing the impact of the chemical reaction between the electrolyte and the surface of the lithium-rich manganese-based positive electrode material under high temperature conditions.

[0063] The main function of high-temperature storage is to accelerate the side reaction between the electrolyte and the lithium-rich manganese-based positive electrode material. The surface interface of the lithium-rich manganese-based positive electrode material is unstable, and the lithium-rich manganese-based positive electrode material will react with the electrolyte, thereby consuming the electrolyte. Usually, the positive electrode material itself has good cycle stability, and there will be no diving phenomenon after 300 to 400 cycles in the withholding system. This evaluation cycle is too long. Through high-temperature storage treatment, it can be differentially controlled within 150 cycles. The worse the surface interface stability, the fewer the number of cycles. The present invention sets a high-temperature storage step, which can accelerate the side reaction between the electrolyte and the lithium-rich manganese-based positive electrode material on the surface of the pole piece, causing a certain loss of the electrolyte, which can accelerate the evaluation process and shorten the evaluation time.

[0064] In some specific embodiments, the pre-charging and pre-discharging treatment method includes: charging the button-type half-cell to 4.4-4.5V, and then discharging it to 3.0-3.5V. For example, the button-type half-cell is charged to 4.4V and then discharged to 3.5V; or, the button-type half-cell is charged to 4.5V and then discharged to 3.5V; or, the button-type half-cell is charged to 4.4V and then discharged to 3.0V.

[0065] In some specific embodiments, the high temperature storage temperature is 60-80°C, including but not limited to any point value of 60°C, 65°C, 70°C, 75°C, 80°C or any range value between two of them. The role of high temperature storage is to accelerate chemical reactions without affecting the intrinsic structure of the material (including binders and conductive agents), so the temperature of high temperature storage is relatively high.

[0066] In some specific embodiments, the high temperature storage time is 2 to 10 hours, including but not limited to any one of 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range between any two of them.

[0067] In some specific embodiments, the activation method includes: performing the activation at a temperature of 45° C. and a voltage range of 2.0 to 4.8 V, with a charge and discharge rate of 0.05 to 0.1 C. The charge and discharge rate may be 0.05 C or 0.1 C.

[0068] In some specific embodiments, the ambient temperature of the high temperature and high voltage cycle test is 45±1°C, such as 44°C, 45°C or 46°C. The ambient temperature of the high temperature and high voltage cycle test is considered to be a high temperature environment commonly used by batteries. The most commonly used test condition is 45±1°C, and the material gas production is due to battery heat, so the working conditions are mostly slightly higher than room temperature.

[0069] In some specific embodiments, the high temperature and high voltage cycle test is performed in an oven.

[0070] In some specific implementations, the voltage range of the high temperature and high voltage cycle test is 2.0 to 4.6 V, and the charge and discharge rate is 0.33 to 1.0 C. For example, the charge and discharge rate may be 0.33 C, 0.5 C, or 1.0 C.

[0071] In some specific embodiments, the button-type half-cell is a lithium-ion button-type half-cell.

[0072] In some specific embodiments, the gas production performance of the lithium-rich manganese-based positive electrode material can be determined by comparing the number of cycles of batteries containing different lithium-rich manganese-based positive electrode materials before water diving occurs. That is, batteries containing different lithium-rich manganese-based positive electrode materials are prepared respectively, and the number of cycles of the batteries after high-temperature storage before water diving occurs is tested respectively, wherein the more the number of cycles, the less the gas production of the corresponding lithium-rich manganese-based positive electrode material, that is, the better the surface and interface stability of the lithium-rich manganese-based positive electrode material.

[0073] It is understandable that the gas production performance of lithium-rich manganese-based positive electrode materials with and without a coating layer on the same substrate can be compared, and the gas production performance of lithium-rich manganese-based positive electrode materials on different substrates can also be compared.

[0074] The method for evaluating the gas production performance of lithium-rich manganese-based positive electrode materials provided by the present invention can be used to evaluate the change in the gas production performance of the material before and after coating modification. The method is simple, easy, fast and effective.

[0075] It can be understood that the specific lithium-rich positive electrode sheet surface density, lithium-rich positive electrode sheet porosity and electrolyte addition amount can be set as needed. When comparing the cycle number data of multiple groups of batteries before the water dive occurs, the control variables (that is, using the same electrode sheet surface density, electrode sheet porosity and electrolyte addition amount) can be used.

[0076] In a second aspect, the present invention provides an application of the method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material in the preparation of lithium batteries.

[0077] The above-mentioned evaluation method of the gas production performance of lithium-rich manganese-based positive electrode materials can screen out lithium-rich manganese-based positive electrode materials with less gas production, which is beneficial to improving the electrochemical performance of lithium batteries.

[0078] In some specific embodiments, the lithium battery comprises a lithium ion battery. The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0079] Example 1

[0080] The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment includes the following steps:

[0081] Using lithium-rich manganese-based positive electrode material Li 1.3 (Ni 0.35 Mn 0.65 )O2 (without coating), with a surface density A of 15 mg / cm 2 , a lithium-rich positive electrode sheet with a porosity B of 35%. The formula of the positive electrode active layer in the lithium-rich positive electrode sheet is: the mass ratio of lithium-rich manganese-based positive electrode material: conductive agent SP: binder PVDF is 90:5:5. The shape of the lithium-rich positive electrode sheet is circular, and the diameter of the lithium-rich positive electrode sheet is 1.2 cm, that is, the radius D is 0.6 cm.

[0082] 15uL of electrolyte is dripped on the surface of the lithium-rich positive electrode (on the positive electrode active layer), and after attaching the separator, 15uL of electrolyte is dripped on the separator, and then the lithium sheet negative electrode is installed to assemble a lithium button half-cell. That is, the volume C of the electrolyte in the button half-cell is 30uL.

[0083] The button-type half-cell is placed in a cabinet for pre-charging and pre-discharging: the button-type half-cell is first charged to 4.4V, then discharged to 3.5V, and then removed.

[0084] The button half-cell was then stored at a high temperature of 60° C. for 2 h (ie, high-temperature storage) to obtain a battery after high-temperature storage.

[0085] Under the temperature condition of 45℃, the voltage range of 2.0~4.8V and the current density of 0.1C, the battery after high temperature storage was activated.

[0086] Subsequently, a 1C cycle test was carried out at a voltage of 2.0 to 4.6 V, and the gas production performance of the lithium-rich manganese-based positive electrode material was determined by the number of cycles before the button half-cell rapidly decayed (i.e., before diving), wherein the number of cycles before the button half-cell rapidly decayed (i.e., before diving) and its gas production are shown in Table 1.

[0087] Example 2

[0088] The evaluation method for the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the surface density A of the lithium-rich positive electrode sheet is 10 mg / cm 2 .

[0089] Example 3

[0090] The evaluation method for the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the surface density A of the lithium-rich positive electrode sheet is 8 mg / cm 2 .

[0091] Example 4

[0092] The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that the porosity B of the lithium-rich positive electrode plate is 38%.

[0093] Example 5

[0094] The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that the porosity B of the lithium-rich positive electrode plate is 40%.

[0095] Example 6

[0096] The evaluation method for the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the volume C of the electrolyte in the button half-cell is 45uL (22.5uL is added to the lithium-rich positive electrode plate and the diaphragm respectively).

[0097] Example 7

[0098] The evaluation method for the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the volume C of the electrolyte in the button half-cell is 60uL (30uL is dripped on the lithium-rich positive electrode plate and the diaphragm respectively).

[0099] Example 8

[0100] The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the high-temperature storage temperature is 70°C.

[0101] Example 9

[0102] The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the high-temperature storage temperature is 80°C.

[0103] Example 10

[0104] The method for evaluating the gas production performance of the lithium-rich manganese-based positive electrode material provided in this embodiment is basically the same as that in Example 1, except that the high-temperature storage time is 6 hours.

[0105] Example 11 to Example 15

[0106] The evaluation method for the gas production performance of the lithium-rich manganese-based positive electrode material provided in Examples 11 to 15 is basically the same as that in Example 1, except that a lithium-rich manganese-based positive electrode material with a coating layer is used (the base material is the same as in Example 1), and the coating layers of Examples 11 to 15 are: TiB2, LATP (lithium aluminum titanium phosphate), Li3PO4, MoS2, and Al2O3, respectively.

[0107] Comparative Example 1

[0108] The evaluation method of the gas production performance of the lithium-rich manganese-based positive electrode material provided in this comparative example is basically the same as that in Example 1, except that the volume C of the electrolyte in the button-type half-cell is 100uL. 50uL is dripped on the lithium-rich positive electrode plate and the diaphragm respectively, and the electrolyte overflows when the button is sealed, so the excess electrolyte will affect the experimental accuracy.

[0109] Comparative Example 2

[0110] The evaluation method for the gas production performance of the lithium-rich manganese-based positive electrode material provided in this comparative example is basically the same as that in Example 1, except that high-temperature storage is not performed.

[0111] Comparative Example 3

[0112] The evaluation method for the gas generation performance of the lithium-rich manganese-based positive electrode material provided in this comparative example is basically the same as that in Example 1, except that the lithium-rich positive electrode plate is not rolled and its porosity B is 75%.

[0113] Comparative Example 4

[0114] The evaluation method of the gas production performance of the lithium-rich manganese-based positive electrode material provided in this comparative example is basically the same as that in Example 1, except that the surface density A of the lithium-rich positive electrode sheet is 20 mg / cm 2 .

[0115] The number of cycles of the button-type half-cells of Examples 1 to 10 and Comparative Examples 1 to 4 before rapid decay (i.e., before water diving) is shown in Table 1.

[0116] Table 1 Cycle times of button-type half-cells before diving

[0117]

[0118]

[0119] It can be seen from Table 1 that the electrode surface density, electrode porosity, electrolyte drop amount, high-temperature side reactions of electrolyte and lithium-rich manganese-based positive electrode materials are related to the number of cycles before the button half-cell dives.

[0120] Therefore, the method for evaluating the gas production performance of lithium-rich manganese-based positive electrode materials provided by the present invention can quickly evaluate the surface and interface stability of lithium-rich manganese-based positive electrode materials and quickly evaluate the gas production performance of lithium-rich manganese-based positive electrode materials. In addition, the present invention controls the surface density and porosity of the lithium-rich positive electrode sheet and the amount of electrolyte added to satisfy the relationship 10≤π×D 2 ×A×100B / C≤25, not only the evaluation process is fast, but also the evaluation result is accurate.

[0121] Furthermore, the number of cycles before rapid attenuation (i.e., before water diving) and the gas production results of the button-type half-cells of Examples 11 to 15 are shown in Table 2.

[0122] Table 2 Verification comparison of different coating processes and corresponding full-electric gas production

[0123]

[0124] It can be seen from Table 2 that the more the electrolyte is consumed, the fewer cycles before the battery dives, and the greater the gas production of the battery.

[0125] The cycle curves of the button-type half-cells of Example 1, Example 11 to Example 15 and Comparative Example 3 are as follows: Figure 1 As shown. By comparing Example 1 and Examples 11 to 15, it can be seen that the cycle performance of the lithium-rich manganese-based positive electrode materials with different coating layers (Examples 11 to 15) are better than that of the lithium-rich manganese-based positive electrode material without a coating layer (Example 1), and the gas production of the lithium-rich manganese-based positive electrode materials with different coating layers (Examples 11 to 15) is lower than that of the lithium-rich manganese-based positive electrode material without a coating layer (Example 1). This shows that the present invention is accurate and effective in evaluating the gas production performance of the lithium-rich manganese-based positive electrode material by the normal number of cycles of the lithium-rich button half-cell. However, the lithium-rich positive electrode plate of Comparative Example 3 has not been rolled, the porosity is too high, and the cycle performance is significantly lower than that of Example 1.

[0126] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for evaluating the gas production performance of lithium-rich manganese-based positive electrode materials, characterized in that: The steps include: The lithium-rich manganese-based positive electrode material is made into a lithium-rich positive electrode plate; the surface density of the lithium-rich positive electrode plate is A, and the unit is mg / cm 2 ; The porosity of the lithium-rich positive electrode plate is B; the shape of the lithium-rich positive electrode plate is circular, and the radius of the lithium-rich positive electrode plate is D, in cm; Add electrolyte to the lithium-rich positive electrode plate and the separator, and assemble them into a button-type half-cell; wherein the volume of the electrolyte in the button-type half-cell is C, and the unit is uL; A, B, C, and D satisfy the following relationship: 10≤π×D 2 ×A×100B / C≤25; The gas production performance of the lithium-rich manganese-based positive electrode material is evaluated by the number of cycles before the button half-cell undergoes water diving.

2. The method for evaluating the gas production performance of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: At least one of the following conditions is met: (1) A is 8 to 15 mg / cm 2 ; (2) The B is 35% to 40%.

3. The method for evaluating the gas generation performance of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The button half-cell is pre-charged and pre-discharged, and then stored at high temperature for a period of time to obtain a battery after high-temperature storage; the battery after high-temperature storage is activated and then subjected to a high-temperature and high-voltage cycle test, and then the gas production performance of the lithium-rich manganese-based positive electrode material is evaluated by the number of cycles before the high-temperature and high-voltage cycle test occurs.

4. The method for evaluating the gas generation performance of lithium-rich manganese-based positive electrode materials according to claim 3, characterized in that: The method of pre-charging and pre-discharging treatment includes: charging the button-type half-cell to 4.4-4.5V, and then discharging it to 3.0-3.5V.

5. The method for evaluating the gas generation performance of lithium-rich manganese-based positive electrode materials according to claim 3, characterized in that: The high temperature storage temperature is 60-80°C; And / or, the high temperature storage time is 2 to 10 hours.

6. The method for evaluating the gas generation performance of lithium-rich manganese-based positive electrode materials according to claim 3, characterized in that: The activation method comprises: performing the activation at a temperature of 45° C., a voltage range of 2.0 to 4.8 V, and charging and discharging at a rate of 0.05 to 0.1 C.

7. The method for evaluating the gas generation performance of lithium-rich manganese-based positive electrode materials according to claim 3, characterized in that: The ambient temperature of the high temperature and high voltage cycle test is 45±1°C.

8. The method for evaluating the gas generation performance of lithium-rich manganese-based positive electrode materials according to claim 3, characterized in that: The voltage range of the high temperature and high voltage cycle test is 2.0 to 4.6 V, and the charge and discharge rate is 0.33 to 1.0 C.

9. The method for evaluating the gas generation performance of a lithium-rich manganese-based positive electrode material according to any one of claims 1 to 8, characterized in that: By comparing the number of cycles of batteries containing different lithium-rich manganese-based positive electrode materials before water diving occurs, the gas production performance of the lithium-rich manganese-based positive electrode material can be determined.

10. Use of the method for evaluating the gas generation performance of lithium-rich manganese-based positive electrode materials according to any one of claims 1 to 9 in the preparation of lithium batteries.